Creating a Bureaucratic Culture to Promote Good Governance - Nur Rohim Yunus; Annissa Rezki; Taryono Taryono (SALAM: Jurnal Sosial dan Budaya Syar-i, 2018)
Bureaucracy is a modern organization that by default enforces the division of labor in its work process. The realization of good governance in Indonesia cannot be separated from the success or failure of the performance of the bureaucracy. The concept of governance simply refers to the decision-making process and its implementation. The realization of good governance or the effectiveness of local government can be seen from its ability to realize programs related to public services. During the new order, the bureaucracy had a big hand in the development process. In the public sector, the concept of bureaucracy is defined as processes and systems that are created rationally to ensure regular, definite and easy-to-control work mechanisms and systems. The role of the bureaucracy in providing services to the community is still not in accordance with the expectations and desires of the community. Bureaucracy develops in line with the political and economic development of a society. In this paper, the author uses a descriptive qualitative methodology.Keywords: Bureaucratic Culture; Good Government; Public AbstrakBirokrasi merupakan organisasi modern yang secara baku memberlakukan pembagian kerja dalam proses kerjanya. Terwujudnya good governance di Indonesia tidak dapat dilepaskan dari berhasil tidaknya kinerja birokrasi. Konsep governance secara sederhana merujuk pada proses pembuatan keputusan dan dan implementasinya. Realisasi good governance atau efektivitas pemerintah daerah dapat dilihat dari kemampuannya dalam mewujudkan program-program yang berkaitan dengan pelayanan publik. Selama orde baru, birokrasi memiliki andil besar dalam proses pembangunan. Dalam bidang publik konsep birokrasi di maknai sebagai proses dan sistem yang diciptakan secara rasional untuk menjamin mekanisme dan sistem kerja yang teratur, pasti dan mudah di kendalikan. Peran birokrasi memberikan pelayanan kepada masyarakat masih belum sesuai dengan harapan dan keinginan masyarakat. Birokrasi berkembang sejalan dengan perkembangan politik maupun ekonomi suatu masyarakat. Dalam penulisan ini, penulis menggunakan metodologi kualitatif deskriptif.Kata Kunci: Budaya Birokrasi; Good Government; Publik